Pengaruh Karakteristik Individu Terhadap Kepuasan Kerja untuk Meningkatkan Kinerja Karyawan - Juliantari, Ni Kadek; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The tight competition in the financial services industry, especially bank financial institutions, encourages every financial institution to improve employee performance so that they can compete and develop. Employee performance problems are also faced by PT. BPR Aruna Nirmaladuta and based on the results of the pre survey, it was found that there were problems related to individual characteristics and job satisfaction. The purpose of this research is to determine the effect of individual characteristics on employee performance directly and mediated by job satisfaction. This research was conducted at PT. BPR Aruna Nirmaladuta, located in Gianyar Regency, involving all 40 employees using the census method. Primary data collection was carried out using a questionnaire which was measured using a five-choice Likert Scale. Hypothesis testing is done by using path analysis and Sobel test to answer the mediating role of job satisfaction. The results of the analysis show that individual characteristics have a positive and significant effect on job satisfaction and employee performance, job satisfaction has a positive and significant effect on employee performance, and job satisfaction mediates the effect of individual characteristics on employee performance